Evaluation of granisetron as an antiemetic in patients undergoing abdominal hysterectomy under spinal anaesthesia - Nikam, Siddharth Uttam; Khandelwal, Prakash N.; Gawali, Ujwala B. (International Journal of Research in Medical Sciences, 2017)
Background: PONV most common complications related to surgery and anaesthesia despite major advances in spinal, epidural and combined spinal-epidural anesthesia techniques IONV are still present in a significant number of patients. Ondansetron, used for controlling PONV induced by chemotherapy or radiation. Recently 5HT3 receptor antagonist granisetron has more potent, selective and longer acting activity than ondansetron. Granisetron is more active for control of PONV in cisplatin induced vomiting than ondansetron. It also reduces PONV in strabismus repair, tonsillectomy, and general surgeries, it has less side effects as compared to ondansetron. Objective of the study was to study efficacy and safety of granisetron and compare it with ondansetron for prevention of IONV and PONV. Methods: 80 ASA grade I and II women undergoing abdominal hysterectomy under spinal anaesthesia were studied. Patients in group A received injection granisetron 2 mg and group B injection ondansetron 4 mg,10 minutes prior to induction of spinal anaesthesia. Main outcome measures were occurrence of nausea, retching or vomiting in intraoperative and postoperative period at 6, 12, 18 and 24 hours’ post-surgery. The response of patient to therapy and side effects were evaluated in both groups. The results were analyzed by ‘z’ test (p<0.5) considered significant. Results: Demographic characteristics of both groups were comparable patients in granisetron (80%) had more complete response as compared to ondansetron (47.5%). Adverse effects were lower in granisetron group. Conclusions: Granisetron 2 Mg has better efficacy and safety profile than ondansetron 4 Mg.